Optimized repetitive transcranial magnetic stimulation techniques for the treatment of major depression: A proof of concept study. (April 2021) - Miron, Jean-Philippe; Voetterl, Helena; Fox, Linsay; Hyde, Molly; Mansouri, Farrokh; Dees, Sinjin; Zhou, Ryan; Sheen, Jack; Desbeaumes Jodoin, Véronique; Mir-Moghtadaei, Arsalan; Blumberger, Daniel M.; Daskalakis, Zafiris J.; et al.
Highlights: rTMS suffers from accessibility issues. We developed new rTMS techniques optimized for increased scalability. Our protocol was safe, well-tolerated and offers several cost-saving opportunities. If rTMS was simplified, it could warrant its use as a first-line treatment in MDD. Abstract: Although effective in major depressive disorder (MDD), repetitive transcranial magnetic stimulation (rTMS) is costly and complex, limiting accessibility. To address this, we tested the feasibility of novel rTMS techniques with cost-saving opportunities, such as an open-room setting, large non-focal parabolic coils, and custom-built coil arms. We employed a low-frequency (LF) 1 Hz stimulation protocol (360 pulses per session), delivered on the most affordable FDA-approved device. MDD participants received an initial accelerated rTMS course (arTMS) of 6 sessions/day over 5 days (30 total), followed by a tapering course of daily sessions (up to 25) to decrease the odds of relapse. The self-reported Beck Depression Inventory II (BDI-II) was used to measure severity of depression. Forty-eight (48) patients completed the arTMS course. No serious adverse events occurred, and all patients reported manageable pain levels. Response and remission rates were 35.4% and 27.1% on the BDI-II, respectively, at the end of the tapering course. Repeated measures ANOVA showed significant changes of BDI-II scores over time. Even though our protocol will require further improvements, some of the concepts we introduced here could help guide the design of future trials aiming at increasing accessibility to rTMS.